Replication Attempt: Measuring Water Conductivity with Polarized Electrodes - Kernbach, Serge (Journal of Scientific Exploration, 2013)
We attempted to reproduce the results of experiments related to measuring the conductivity of water with deeply polarized electrodes. As proposed in the original works, the polarized electrodes are sensitive to a high-penetrating emission generated by objects of different origin. We demonstrate the experiment setup used and the results obtained in replication and control experiments. Based on the trials carried out, we judge the results of this replication to be positive.